2008
DOI: 10.1063/1.2836791
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic calculation of spin wave propagation for magnetologic devices

Abstract: The propagation of magnetic wave packets in magnetic nanowires was calculated as a function of wire width, field strength, field ramp time, field area size, and geometry of a magnetic nanowire. Spin waves are excited locally by applying a small perturbation in the magnetization in a 20nm wide region. A wave packet is emitted from the input region and travels along the wire with a velocity of 740m∕s. The finite element micromagnetic simulations show that wave packets can be guided along a bent nanostructure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Bance et al reported the transmission of backward-volume (BV) spin-wave packets through a 90° circular bend without losses8; nevertheless they did not identify the mode distribution of these spin waves, which is essential to understand the spin-wave propagation inside the bend. Quite recently, Dvornik et al demonstrated the fact of the BV spin waves to follow a curved waveguide without noticeable losses at the bend7, and thus claimed that the spin waves adapt the bend with their wave vectors parallel to the local magnetization.…”
mentioning
confidence: 99%
“…Bance et al reported the transmission of backward-volume (BV) spin-wave packets through a 90° circular bend without losses8; nevertheless they did not identify the mode distribution of these spin waves, which is essential to understand the spin-wave propagation inside the bend. Quite recently, Dvornik et al demonstrated the fact of the BV spin waves to follow a curved waveguide without noticeable losses at the bend7, and thus claimed that the spin waves adapt the bend with their wave vectors parallel to the local magnetization.…”
mentioning
confidence: 99%
“…(32) into Eq. (18) and using Eqs (33). and(35), the corresponding PDE to u ð2Þ r ðr; sÞ with its initial and boundary conditions separation of variable technique and reminding that u ð2Þ r should be bounded at the revolution axis points of the nanowire, ðsÞJ a n ðb n rÞ;…”
mentioning
confidence: 99%
“…These are complemented by efforts to compute the magnetization dynamics in various kinds of magnonic crystals and waveguides, of different geometries and made of different materials [5]- [7]. The dispersion relation, ω(k), provides valuable insights into the characteristics of propagating spin waves (SWs), and aids in our pursuit of building functional devices around magnonic waveguides [8]- [10]. Dispersion relations have traditionally been obtained using experimental means, which often means multiple experimental runs and associated costs and delays.…”
Section: Introductionmentioning
confidence: 99%